Case Studies of Attacks over Adaptive Modulation Based Tactical Software Defined Radios - David Fernandes Cruz Moura; Fabricio Alves Barbosa da Silva; Juraci Ferreira Galdino (Journal of Computer Networks and Communications)
This paper presents case studies of attacks aimed at tactical software defined radios based on a classification with the most common sources of vulnerabilities, classes of attacks, and types of intrusions that military radio sets may suffer. Besides that, we also describe how attack mitigation strategies can impact the development of SDR infrastructures. By using such approach, we identify several possible sources of vulnerabilities, attacks, intrusions, and mitigation strategies, illustrating them onto typical tactical radio network deployment scenarios, as an initial and necessary step for the definition of realistic and relevant security requirements for military software defined radio applications.